The Determinants of Employee Performance at the DPRD Secretariat in Medan City: The Role of Work Discipline, Motivation, and Job Satisfaction - Pratama, Nugraha; Pasaribu, Fajar; Jufrizen, Jufrizen; Rahmat, Muhammad; Rialdy, Novien (Journal of International Conference Proceedings, 2025)
This study aimed to investigate the extent to which internal organizational factors influence employee performance, with a particular focus on work discipline, motivation, and job satisfaction. The research adopted a quantitative method combined with an associative analytical approach to evaluate the relationships among these variables. The population involved in this study consisted of all civil servants employed at the DPRD Secretariat of Medan City, totaling 51 individuals. Given the manageable size of the population, the study applied a saturated sampling technique, meaning every member of the population was included as a respondent. Data were analyzed using SPSS Version 29. The results indicated that both work discipline and motivation had a statistically significant effect on employee performance, while job satisfaction did not yield a meaningful influence when examined independently. These findings suggest that high levels of discipline and strong motivation contribute positively to enhancing employee performance. Moreover, when examined collectively, work discipline, motivation, and job satisfaction were found to have a significant combined effect, demonstrating that the integration of these factors plays a crucial role in strengthening overall performance among civil servants within the DPRD Secretariat.